Fire effects on vegetation in a grassy dwarf shrubland at a site in the eastern Karoo, South Africa - du Toit, Justin CO; van den Berg, Loraine; O'Connor, Tim G (African journal of range & forage science, 2015)
Fire is rare in semi-arid eastern Karoo dwarf shrublands, South Africa, and responses to fire are largely unknown. Recent increased grassiness, and hence fuel loads, at Grootfontein in the Eastern Cape allowed an accidental fire (24.3 ha) to carry, and afforded the opportunity to examine compositional and structural effects of fire on a grassy dwarf shrubland. Sampling seven months after the fire, 108 species (102 perennial) were encountered, of which 74 were resprouters, six were fire sensitive (non-sprouters), and the remainder (rare, non-perennial or herbaceous) had an unknown response. The dominant pre-fire shrub, Eriocephalus ericoides, was extirpated by the fire, as was the unpalatable and sometimes invasive Ruschia intricata. All grass species resprouted, and grass became the dominant life-form after the fire, indicating a possible conferred competitive advantage. Resprouting shrubs grew to only a small fraction of their pre-burn size. The unpalatable, aromatic shrub Stachys rugosa was the dominant post-burn shrub. Extirpated species will need to regenerate from seeds, but no seedlings were found in the gaps where shrubs had stood. The widespread ability to resprout confers resilience on this vegetation, but fire does induce changes in structure, in the dominance of life forms, and it decreases canopy cover.